Analyzing John Dewey's learning theory in pragmatism and existentialism (MMIT Proceedings, 2025)
This article presents a comparative analysis of John Dewey's learning theory in the context of pragmatism and existentialism. Key aspects of Dewey's approach to education are explored, emphasizing his understanding of the learning process as an active interaction between the learner and the world around him. Pragmatism, as a philosophical tradition, emphasizes the importance of experience and practical outcomes in the educational process, while existentialism emphasizes individual existence, freedom of choice, and responsibility. The article examines the intersections and differences between these approaches in the context of educational practice, as well as their influence on the formation of the modern educational process. Contemporary research and literature reflecting the relevance of Dewey's ideas in a rapidly changing world are analyzed. Finally, the importance of integrating pragmatic and existential aspects into educational practices to create a more flexible and adaptive educational environment is emphasized